Radialistunnelsyndrom/Supinatorlogensyndrom: Dekompression über den anterolateralen Zugang : operative Techniken - Flock, Florian; Unglaub, Frank; Müller, Lars Peter; Leschinger, Tim; Spies, Christian (Operative Orthopädie und Traumatologie, 2025)
Objective Treatment of pain and hypaesthesia caused by radial tunnel syndrome and functional deficits caused by supinator lodge syndrome. The objective for chronic nerve compression is containment to prevent further damage. Indications Radial tunnel syndrome, supinator lodge syndrome, tumour compressing the nerve, unsuccessful conservative therapy for at least 6 weeks and up to 4-6 months. Contraindications Infection or skin disease at the surgical area, severe scarring from previous surgery, systemic diseases that prevent anaesthesia, and nerve entrapment outside the radial tunnel and supinator tunnel. Surgical technique Decompression of the radial nerve both by addressing the entrapments within the radial tunnel and incising the supinator tunnel facilitating the anterolateral approach via the internerval plane between the brachioradialis and brachialis muscles. Postoperative management Compressive dressing around the complete arm for 3 weeks. Results Radial tunnel syndrome (RTS) and supinator lodge syndrome are nerve compression syndromes of the radial nerve. Proximal compression may cause mixed symptoms with pain, sensory, and motor deficits, while distal compression may cause either sensory or motor deficits. If symptoms persist for 4-6 months, surgical decompression is recommended, whereby the anterolateral approach is preferred due to better healing results and extensibility. The success rate after surgical decompression averages between 67 and 92%.